Musical identities of older adults are not easily changed: an exploratory study. (27th May 2019) - Woody, Robert H.; Fraser, Amy; Nannen, Briana; Yukevich, Polly
ABSTRACT: We explored the role of self-efficacy in participatory music-making, and whether a single such music-making activity could make non-musician adults more open to seeing themselves as musical. Past research has suggested that even recipients of multiple years of school music education do not consider being musical as a part of their identity, and they do not exit adolescence with an independent musicianship that would facilitate their making music as adults. In our study, we invited older adults to participate in an informal music-making experience designed to be participatory and enjoyable. A questionnaire measured musical beliefs and self-perceptions before and after the music activity. The posttest version included items through which participants indicated their self-efficacy during the activity. Data analysis revealed that across the entire sample, the average rating of how musical they considered themselves to be did not change significantly, but there was a significant jump in their reported likelihood of engaging in a collection of musical life activities. Specifically, there was a rise in the likelihood of playing musical instruments informally. The study's most important finding was that participants with higher self-efficacy during the activity emerged from it believing themselves to be more musical than they had previously thought.